Cheilectomy With or Without Cryopreserved Umbilical Cord for Hallux Rigidus: A Prospective Randomized Controlled Trial. Issue 4 (16th October 2019) - Heintzman, Sara; Ferguson, Chad; Davis, W. Hodges; Anderson, Robert B.; Cohen, Bruce E.; Jones, Carroll P.; Odum, Susan M.; Ellington, J. Kent
Category: Midfoot/Forefoot Introduction/Purpose: Arthritis of the first MTP joint (hallux rigidus) is the most common form of osteoarthritis affecting the foot. Despite advances in interpositional techniques and devices, dorsal cheilectomy remains part of the treatment algorithm after failed conservative treatment of hallux rigidus. Dorsal cheilectomy aims to surgically remove dorsal impingement and improve pain and function as well as range of motion. However, prospective data on outcomes following this procedure is lacking. Cryopreserved umbilical cord (UC) allografts have been shown to mitigate inflammation and decrease scar formation. This has theoretical benefit for recovery and disease progression following dorsal cheilectomy. In the first prospective randomized and blinded cheilectomy trial reported, we aimed to compare outcomes of patients undergoing dorsal cheilectomy alone and dorsal cheilectomy with cryopreserved umbilical cord. Methods: After obtaining institutional board review approval, patients were randomized to cheilectomy alone(CA) or cheilectomy with cryopreserved UC. Surgeries were performed by fellowship trained surgeons. Dorsal cheilectomy was performed utilizing fluoroscopy to remove ˜25% articular surface. UC was applied to cheilectomy site and secured inside capsule with absorbable "stay-stitch." Patients were followed for 1 year with AOFAS MTP-IP, Foot Function Index (FFI), and VAS-pain (walking, waking, and end of day) outcomes collected preoperatively and at 6 months and 1 year. In addition, radiographic range of motion data was collected (maximal dorsiflexion and plantarflexion). Power analysis determined 27 patients per group was needed to detect a significant difference between AOFAS scores of 95(UC) and 85(control). Data was analyzed utilizing statistical analysis software(SAS v9.4). AOFAS MTP-IP, FFI, and VAS scores were analyzed using Wilcoxon signed-rank test. Range of motion data was analyzed using two-way ANOVA with Tukey adjusted least square means test. Results: 51 patients (26 UC, 25 CA) completed the study. There were 5 bilateral surgeries in UC group and 2 in CA group, totaling 31 and 27 feet respectively. Post-operatively, UC group had significantly improved AOFAS and FFI scores at 1 year compared to CA group. There was no difference between groups for VAS-pain scores (walking, waking, or end of day at any time point), but overall VAS-pain improved in both groups from preoperative values. There was no difference seen in range of motion between groups. However, there was an overall improvement in maximal plantarflexion at 6 months and 1 year and maximal dorsiflexion at 6 months in both groups. Conclusion: We present the results of the first randomized and blinded prospective study of cheilectomy surgery patients. There was improvement in range of motion, pain, AOFAS, and FFI scores in all patients with statistically significant improvement at 1 year in AOFAS and FFI scores in the UC group compared to CA group. When appropriately selected, cheilectomy remains a good option for patients with symptomatic hallux rigidus. Cryopreserved umbilical cord is a potential adjuvant to cheilectomy to modulate inflammation and scarring with early 1 year results showing improvements in functional outcome scores.